Stereoconvergent Amine-Directed Alkyl–Alkyl Suzuki Reactions of Unactivated Secondary Alkyl Chlorides - Lu, Zhe (2011)
A new family of stereoconvergent cross-couplings of unactivated secondary alkyl electrophiles has been developed, specifically, arylamine-directed alkyl–alkyl Suzuki reactions. This represents the first such investigation to be focused on the use of alkyl chlorides as substrates. Structure-enantioselectivity studies are consistent with the nitrogen, not the aromatic ring, serving as the primary site of coordination of the arylamine to the catalyst. The rate law for this asymmetric cross-coupling is compatible with transmetalation being the turnover-limiting step of the catalytic cycle.